2002
DOI: 10.1186/1475-2875-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and expression of a PP1 serine/threonine protein phosphatase (PfPP1) from the malaria parasite, Plasmodium falciparum: demonstration of its essential role using RNA interference

Abstract: BackgroundReversible protein phosphorylation is relatively unexplored in the intracellular protozoa of the Apicomplexa family that includes the genus Plasmodium, to which belong the causative agents of malaria. Members of the PP1 family represent the most highly conserved protein phosphatase sequences in phylogeny and play essential regulatory roles in various cellular pathways. Previous evidence suggested a PP1-like activity in Plasmodium falciparum, not yet identified at the molecular level.ResultsWe have id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…All of the pET15b clones were introduced into Escherichia coli BL21(DE3) pLysS and induced by isopropyl 1-thio-␤-D-galactopyranoside. The soluble N-terminally His-tagged recombinant proteins were purified by Ni 2ϩ -affinity chromatography using the HisBind TM kit (Novagen) (15). The CyP and FKBP domains of TgFCBP57 were similarly expressed and purified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the pET15b clones were introduced into Escherichia coli BL21(DE3) pLysS and induced by isopropyl 1-thio-␤-D-galactopyranoside. The soluble N-terminally His-tagged recombinant proteins were purified by Ni 2ϩ -affinity chromatography using the HisBind TM kit (Novagen) (15). The CyP and FKBP domains of TgFCBP57 were similarly expressed and purified.…”
Section: Methodsmentioning
confidence: 99%
“…RNAi-like effect in the Apicomplexa as well, especially in T. gondii (15,20,29,30). We adopted a similar approach and targeted the TgFCBP57 mRNA by transfecting a dsRNA corresponding to an internal 500-bp region of the coding sequence, which led to successful silencing of TgFCBP57 (Fig.…”
Section: Inhibition Of T Gondii By Csa and Fk506 -mentioning
confidence: 99%
“…The use of potent inhibitors of phosphatases showed that P. falciparum predominantly expressed PP1-like activity which appears to control parasite growth and seems to be involved in the release of infectious merozoites [19,20]. In the past decade, a vast body of research has provided converging evidence that the key mechanism of the mode of action of the PP1c subunit resides in the presence of interacting regulators that direct the proper functions of this phosphatase (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, dsRNA has been reported to affect the growth of P. falciparum in culture [28]. Some studies have suggested that the inhibition of growth is due to classic RNA interference pathway [29][30][31][32], whereas others have reported that this is due to an antisense effect [32][33][34]. It is noteworthy that on closer examination of the genome of Plasmodium, it was not possible to identify the homologues of the genes of the components of the classic RNA interference pathway [32].…”
Section: Discussionmentioning
confidence: 99%